1990
DOI: 10.21273/jashs.115.4.654
|View full text |Cite
|
Sign up to set email alerts
|

Anti-senescence Activity of Chemicals Applied to Kentucky Bluegrass

Abstract: This study was conducted to determine the potential anti-senescence activity of certain chemicals by monitoring changes in gross. CO2 exchange with senescence of excised leaves of Kentucky bluegrass (Poa pratensis L.). One day following foliar applications of benzyladenine (BA), triadimefon, and propiconazole, with and without chelated Fe (8% Fe phosphate citrate), Kentucky bluegrass leaves were excised, floated on distilled water in petri dishes, and pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
17
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 9 publications
3
17
0
Order By: Relevance
“…Spraying with fulvic acid increased the yield of wheat grown at dry conditions to 97% of the irrigated control (Xudan 1986). In semi-arid conditions, foliar application with humic acid represented an alternative to conventional soil fertilization (Delfine et al 2005), stimulated shoot and root growth, and improved resistance to environmental stress in plants (Goatley and Schmidt 1990). Under water stress, foliar fertilization with humic molecules increased leaf water retention and the photosynthetic and antioxidant metabolism (Jiu, Qi, and Sheng 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Spraying with fulvic acid increased the yield of wheat grown at dry conditions to 97% of the irrigated control (Xudan 1986). In semi-arid conditions, foliar application with humic acid represented an alternative to conventional soil fertilization (Delfine et al 2005), stimulated shoot and root growth, and improved resistance to environmental stress in plants (Goatley and Schmidt 1990). Under water stress, foliar fertilization with humic molecules increased leaf water retention and the photosynthetic and antioxidant metabolism (Jiu, Qi, and Sheng 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous cytokinins have been shown to increase endogenous cytokinin content, and NR and to improve plant stress tolerance. Goatley and Schmidt (1990) reported that foliar application of 6‐benzyladenine (6‐BA) delayed senescence of Kentucky bluegrass ( Poa pratensis L.). Liu et al (2002) noted that rootzone injection of zeatin riboside increased endogenous cytokinins and antioxidant activity and delayed senescence in heat‐stressed creeping bentgrass.…”
mentioning
confidence: 99%
“…Thimann (1987) found that cytokinins delay senescence processes probably by maintaining the integrity of the tonoplast membrane. Goatley and Schmidt (1990) reported that foliar application of 6-benzyladenine (6-BA) delayed senescence of Kentucky bluegrass. Liu et al (2002) noted that rootzone-injection of zeatin riboside increased endogenous cytokinins, antioxidant activity, and delayed senescence in heat-stressed creeping bentgrass.…”
mentioning
confidence: 99%